Artificial Intelligence-Driven Disintermediation and Transformations in Commercial Property and Casualty Insurance - Saltzstein, Michael J. (Digital Repository of Theses, 2026)
This dissertation examines how Artificial Intelligence (AI) disintermediation is evolving the Commercial Property and Casualty (P&C) insurance industry, in terms of operational improvements, changes in the role in intermediary services, customer perceptions, and regulatory issues. The work looks at how AI is used to transform key processes like underwriting, claims processing, marketing, policy issuance, premium collection, client communication, broker and agent services and customer service - and the role that AI has played in reducing the importance of traditional intermediaries. A mixed-methods approach was adopted, which combined a quantitative survey of 196 industry professionals to a content analysis of more than 200 academic, corporate and regulatory documents to be content analyzed qualitatively. The quantitative analysis looked at the efficiencies, accuracy and speed of AI in critical insurance functions while the qualitative analysis brought more insight into the operational, regulatory and ethical dimensions of adopting AI. The results shows that AI has catch significant gains of efficiency, speed, and accuracy, especially the claims processing and underwritten areas. The findings are conclusive of few perceived gain by both Intermediaries and Policy Holders, Gains include accuracy of claim reporting and management, underwriting processes, a measurable decrease in time to conduct these activities and, perhaps most applicable to the intermediaries, a reduction in servicing and marketing costs. This dissertation’s qualitative and quantitative findings are a way into the current status of AI in the P&C industry and help to see current challenges in its implementation, regulation and acceptance. These findings are immediately applicable to both intermediaries and policyholders as each continues their evolution through the fast-paced growth and evolution of AI itself and its impacts on the P&C Insurance Industry as a whole. These ongoing areas of opportunity should continue the disintermediation of the P&C insurance industry and the resulting decrease in both manual processes and a significant increase in cost efficiency. Keywords: Artificial Intelligence (AI), Property and Casualty Insurance (P&C), Disintermediation, Operational Efficiency, Insurance Transformation